2016
DOI: 10.4236/health.2016.84035
|View full text |Cite
|
Sign up to set email alerts
|

The Outcome of Midwife-Mother Relationship in Delivery Room: A Qualitative Content Analysis

Abstract: Effective communication and emotional support of parturient women improve the outcome of childbirth. Reduction in Duration of labor, cesarean rate, use of anesthesia, and 5 minute Apgar Score less than 7 can achieve. This study was a part of a large mixed method study during 2013-2014. In this qualitative study, in-depth interviews were conducted with 32 participants (16 mother and 16 midwife), using semi-structured interviews. Participants were recruited by purposive sampling with maximum diversity in terms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 16 publications
2
21
0
1
Order By: Relevance
“…The results of the present study are similar to results of other studies done in different countries which also show the importance of women's satisfaction with communication as an important factor in the general satisfaction of women's birth care [20][21][22]. In a descriptive study from Iran, 50 midwives were evaluated by parturient women.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results of the present study are similar to results of other studies done in different countries which also show the importance of women's satisfaction with communication as an important factor in the general satisfaction of women's birth care [20][21][22]. In a descriptive study from Iran, 50 midwives were evaluated by parturient women.…”
Section: Discussionsupporting
confidence: 89%
“…In a qualitative study on 16 mothers in Iran, results show that outcomes of a positive midwifemotherrelationship in the delivery room can lead to facilitation of childbirth, a positive birth experience, mental health promotion and improvement in the mother's quality of life. An effective midwife-mother relationship can lead to positive childbirth outcomes and promotion of maternal and neonatal health [21].…”
Section: Discussionmentioning
confidence: 99%
“…An accompanying midwife acts as an important and reliable source of support in stressful situations, which can increase the resilience of pregnant women. A midwife's contemplation and attention to duties can also reflect on pregnant women who are impatient and not resilient, which further clarifies the benefits of an accompanying midwife (32)(33)(34). Our results also showed that having an accompanying midwife could influence delivery preference in pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the mothers who have experienced delivery in both centers have suggested a more intimate relationship between them and midwives in comparison to the gynecologists, which increased the trust of mothers in the care team, and also the comfort of mothers before, during and after delivery. Process factors can significantly reduce the anxiety of mothers before, during, and after delivery, [34][35][36] strengthen maternal and infant health indicators, and increase maternal satisfaction with the health care provider. [37][38][39] Outcome factors…”
Section: Structural Factorsmentioning
confidence: 99%